2020
DOI: 10.1007/s12103-020-09533-5
|View full text |Cite
|
Sign up to set email alerts
|

When Stay-at-Home Orders Leave Victims Unsafe at Home: Exploring the Risk and Consequences of Intimate Partner Violence during the COVID-19 Pandemic

Abstract: The novel coronavirus pandemic (hereafter COVID-19) is likely to have unprecedented impacts on the incidence and impacts of crime and violence globally. This includes impacts to the risk, consequences, and decisionmaking of women experiencing violence by an intimate partner (hereafter IPV). Most importantly, the COVID-19 pandemic, and its impact on the risk of IPV is likely to differentially impact vulnerable populations, including minority women and those with long histories of victimization and mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
193
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(210 citation statements)
references
References 22 publications
9
193
1
7
Order By: Relevance
“…Following the lead of previous reviews, also in our work we found a sharp spike in DV cases reported around the globe (Agüero 2020; Baig et al 2020;Barbara et al 2020;Boserup et al 2020;Bradley et al 2020;Chandan et al 2020;Gebrewahd et al 2020;Ghoshal et al 2020;Goh et al 2020;Gosangi et al 2020;Jarnecke et al 2020;Jetelina et al 2020;Kaukinen et al 2020;Kofman et al 2020;Kumar 2020;Leslie et al 2020;Mahase et al 2020;Mazza et al 2020;Neil 2020;Nigam 2020;Piquero et al 2020;Qin et al 2020;Roesch et al 2020;Roseboom et al 2020;Sifat 2020;Telles et al 2020;Tochie et al 2020;Vieira et al 2020;Yahya et al 2020;Zargham et al 2020). For example, Aguero (2020) in a study conducted in Peru, one of the several countries which imposed a national lockdown in March, found that the incidence rate of calls to helplines centres increased around 48% between April and July 2020.…”
Section: Resultssupporting
confidence: 81%
“…Following the lead of previous reviews, also in our work we found a sharp spike in DV cases reported around the globe (Agüero 2020; Baig et al 2020;Barbara et al 2020;Boserup et al 2020;Bradley et al 2020;Chandan et al 2020;Gebrewahd et al 2020;Ghoshal et al 2020;Goh et al 2020;Gosangi et al 2020;Jarnecke et al 2020;Jetelina et al 2020;Kaukinen et al 2020;Kofman et al 2020;Kumar 2020;Leslie et al 2020;Mahase et al 2020;Mazza et al 2020;Neil 2020;Nigam 2020;Piquero et al 2020;Qin et al 2020;Roesch et al 2020;Roseboom et al 2020;Sifat 2020;Telles et al 2020;Tochie et al 2020;Vieira et al 2020;Yahya et al 2020;Zargham et al 2020). For example, Aguero (2020) in a study conducted in Peru, one of the several countries which imposed a national lockdown in March, found that the incidence rate of calls to helplines centres increased around 48% between April and July 2020.…”
Section: Resultssupporting
confidence: 81%
“…Survivors have multiple priorities to consider when accessing services and likely employ myriad strategies to gain safety and security in both the short- and long-term (Hanson et al 2019 ). As such, mandatory stay-at-home orders, quarantine protocols, and social distancing recommendations may increase the frequency and severity of IPV and risk for sexual assault (Boserup et al 2020 ; Kaukinen 2020 ; Mazza et al 2020 ). Further, perpetrators of abuse may use this increased isolation and social distancing restriction to exercise power and control over their partner, further reducing the survivor’s ability to access formal and informal services (World Health Organization (WHO) 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Globally, the COVID-19 pandemic has impacted nearly all aspects of daily life, from interacting with informal support networks to accessing routine healthcare. An overlooked consequence of the pandemic is the increased risk of intimate partner violence (IPV) and sexual assault, resulting negative impacts, and the ability of survivors to access supportive services (Boserup et al 2020 ; Kaukinen 2020 ). The novelty and speed of the COVID-19 pandemic has drastically altered the lives of survivors of violence, bringing new challenges and concerns alongside existing inequities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 has led to the potential of enhanced risk for increased IPV due to factors such as forced co-existence with the abuser, and financial stress. Further, in some world regions, emerging evidence suggests that the COVID-19 outbreak has also curtailed access (Fraser, 2020) as well as help-seeking by survivors (Kaukinen, 2020). Immigrant women, a group disproportionately affected by IPV and IPV-related homicides , may be at even further risk for IPV and its consequences.…”
mentioning
confidence: 99%